Análise de vegetação e solos em áreas de nascentes da Sub-Bacia Hidrográfica do Rio Piauitinga, Sergipe - Freire, Gilmara da Silva (2019)
The ciliary vegetation is a strip of forest limited to the springs and border of the courses and reservoirs of water, being present in the regions in which the original vegetation of interflow is also forest. This is fundamental to the maintenance of environmental stability, functioning as ecological corridors. When present along the waterways and linked by nearby forest fragments, they provide passage of animals, facilitating the dispersal of seeds. Despite its importance, the pace of deforestation around springs and river banks is accelerating. In this way, this study was carried out with the objective of analyzing the structure, composition and floristic similarity, as well as analyzing the successional classes, the dispersion syndromes of the species and the correlation between the edaphic factors and the distribution of the species the shrub component -arboreal in areas of springs, a total of 57, located in the municipalities of Estância, Salgado, Lagarto and Boquim, in the Hydrographic Sub-Basin of Piauitinga River, in Sergipe state, Brazil. Initially, a complete list of the species identified in the studied municipalities was elaborated, and the diversity, dispersion syndromes and floristic similarity were analyzed. The pH, K, Na, Ca + Mg, Ca, Mg, Al, H + Al, P and MO were determined in relation to the edaphic factors, SB, V, PST, CTC, and the determined soil grading (sand, clay and silt). In addition, it performed a canonical correspondence analysis (CCA) to verify if edaphic factors influence the pattern of distribution of species throughout this planning unit. Regarding the floristic composition of the 57 springs studied, 139 species were identified in 101 genera and 47 botanical families. The most representative families were Fabaceae (27 species) and Myrtaceae (18 species). In relation to the dispersion syndromes, there was predominance of zoocoria, observed in 103 species. The similarity values were considered low, that is, less than 50%, and the springs that showed the greatest similarity among themselves were located in the municipalities of Salgado and Boquim (40%), forming a subgroup. Although the fragments, which correspond to the surrounding areas of the springs, are anthropized, they have a significant richness in the floristic composition, which is of great importance for the maintenance of ecological processes in the ecosystems of the Piauitinga River Sub-Basin. In addition, they can surely serve as a basis for the use of the listed species in future forest recovery/restoration projects, both in the spring and in the watercourse areas of this planning unit. As for the chemical and granulometric properties of the soil, a significant difference (P <0.05) was observed in Ca + Mg, Ca, CTC, PST, sand and clay content in the 0-20 cm depth. As for depth 20-40 cm, there was a significant difference between Al, PST, sand and clay. No significant difference was observed for the other factors. The analysis of canonical correspondence showed that variations in soil chemical and granulometric attributes influence the spatial distribution of shrub-tree species along the planning unit studied.